Death of a Tyrant? From Liberation Fighter to Deposed Leader? Frames of Robert Mugabe's Death in Selected Zimbabwean and British Media - Tendai Owen Chikara; Collen Sabao; Moses Magadza (LAN Publishers, 2023)
The chapter, in attempting to configure the enigma that Mugabe is, comparatively analyse the framing of his death in Zimbabwean and British newspapers. The chapter makes a comparative discourse analytic and framing analysis of news reports breaking the death of Mugabe in British and Zimbabwean newspapers. In doing this and through the Framing Theory (Entman, 1996), the chapter demonstrates how Mugabe possessed a multiplicity of political personas as he is imaged in diverse and conflicting ways in different media, based on their content and context. Drawing from the elusive nature of his description, The chapter responds to the question of whether the apt description of Mugabe should be that of a liberation war hero to be celebrated. The chapter observes that the diverse ways in which Mugabe is framed can only be understood within the context of the history between Britain and Zimbabwe on the one hand (in order to understand the frames in British media) and political history and developments in Zimbabwe since the turn of the millennium (to be a able to appreciate the frames in Zimbabwean newspapers) on the other. Frames in British media, which largely and collectively vilify Mugabe on whatever pretext as a murderer, despot and tyrant under the guise of being the voice of reason and democracy, the chapter argues, are shaped by historical relations between Zimbabwe and her colonial master that have degenerated over the years into one characteristic by an insult hurling contest. On the other hand, frames in Zimbabwean newspapers can only be understood in the context of the media polarity in Zimbabwe that was birthed by the growth of populist oppositional politics as well as newspaper ownership patterns in Zimbabwe.